SISTEM PENUNJANG KEPUTUSAN PENILAIAN KINERJA KARYAWAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA PT. LIEBRA PERMANA JAKARTA - Novianny, Vanny; Heriyanto (Universitas Majalengka, 2023)
The employee performance appraisal process is a complex process and requires careful consideration. Employee performance appraisal at PT. Liebra Permana Jakarta is carried out by looking at several criteria such as the value of Attendance, Performance, Discipline, and Initiative. However, the system at PT. Liebra Permana Jakarta is still manual, therefore the authors are trying to create a Decision Support System program in evaluating employee performance using the website-based PHP and MySQL programming languages. This system has a better advantage when compared to manual calculations. The method used in assessing employee performance is by using the Simple Additive Weighted (SAW). The results of this study apart from the DSS application website are calculations using the Simple Additive Weighted method, with reference to the criteria for Absence, Performance, Discipline and Initiative, normalization and ranking, the best employee with the highest score is Felicia.